The Leadership Capacity of Primary School Principals from the Perspective of Collaborators - WajidAbboud, M. A. Khadija (International Journal of Psychosocial Rehabilitation, 2020)
Management is leadership, and leadership is a process of influencing others and management leadership, like management itself is not talent or art but is based on basic rules and principles that the leader must be familiar with until he reaches a leadership position that enables him to influence others, and change their administrative behavior in the desired manner and from Here leadership has become a necessary basis for any field of societies, and educational management is one of the most important in societies that are concerned with building individuals and societies. The sample of the research represents a community of primary school principals to raise the first Rusafa between males and females.Primary education is one of the means in preparing the human element to achieve ambitions in social development, and the primary school is one of the means of education to prepare cadres.The human wealth has a great importance that exceeds its importance, natural resources, and material capabilities, as these resources and capabilities cannot be used effectively in the progress of the country without the presence of the human being able to use them, and education is the means in the hands of society to prepare and develop the human element to achieve its ambition in economic and social development.